MEMBRANE CONTACTOR MODULE DESIGN FOR FLUE GAS CLEANING - MAIRIZA , LIA
Membrane based processes are optiol1s rapidly gaining recognition as efficient and compact separation technologies recently, so that they are cOl1sidered as a prospective alternative for flue gas cleaning to replace conventional separation processes. One of the major parameters determining succesfull of membrane based processes is module design The objective of this work is to design a transversal module for membrane contactor that is applied for flue gas cleaning. Transversal module gives higher turbulence compared to longitudinal module and will increase mass transferfer coefficient. Perpendicular flow of transversal module promotes eddy circulation and decreases the length of boundary layer along memhrane module. Therefore, obtained flux is greater in transversal module. Nevertheless, at lower sorbent flow rate, ohtained flux from both modules at maximum and minimum gas flow rate show the similar values. In transversal module, ohlained flux when gas flowing through the shell side were higher thall those if gas flowing through the lumen.